Design of a wireless battery charger for cellular phone - Ibrahim, Mohd Basri Faris (2012)
This paper present about the identification of circuit with a new technique of charging the lithium-ion battery for a Cellular phone using wireless. Inductive Power Transfer (IPT) refers to the concept of transferring electrical power between two isolated circuits across an air gap. IPT system can be divided into two parts; primary and secondary. The primary side (Transmitter) of the system is made up of a forward resonant converter and a coil. This power supply produces a high frequency sinusoidal current in the coil. The secondary side or receiver has a smaller coil, and a converter to produce a DC voltage. The primary circuit was set up as the charger unit with the winding coil which have different shape and structure compared to the secondary circuit respectively, which is adopted as a wireless energy transfer device. Primary circuit act as the transmitter transfer sufficient inductive power to the secondary circuit which become as the receiver. The secondary side is in the telephone unit received enough power to charge the cellular phone. The energy power transfer between these primary and secondary circuit is verified from the experiment result. The analysis of the primary side of circuit with is performed and the design optimization is presented. A simple circuit for secondary side for battery charging is presented and the analysis is presented.